On writing : a memoir of the craft - King, Stephen, frey50 (New York : Scribner, 2000)
This volume "really contains two books: a fondly sardonic autobiography and a tough-love lesson for aspiring novelists", written by American author of contemporary horror, suspense, science fiction and fantasy, Stephen King (b. 1947). The first third of the book contains King's memoir, which includes heartfelt tidbits about his brother, mother and his long battles with alcohol and drug addiction. The second part of the book, "On Writing," is where aspiring novelists might find inspiration. King describes the symbolism in many of his novels and offers writers common sense advice. He presents his taboos of writing: adverbs (especially those in dialog) and the passive voice. He describes his writer's toolbox, including examples of both good and bad writing, sometimes taken from his own work, sometimes taken from other writers. He also describes his approach to research. King concludes by including a list of nearly a hundred novels that he considers the best that he's read in the last three or four years.
Keywords: King, Stephen, -- 1947-; Authors, American -- 20th century -- Biography; Horror tales -- Authorship